THE ACTUALIZATION OF THE INCREASED COMPETITIVENESS OF OIL PRODUCTS RUB HERBACEOUS TRADITIONALLY THROUGH BRANDING AND CERTIFICATION OF PRODUCT QUALITY ASSURANCE UMK RAMBAL DELI IN KECAMATAN GALANG - Thohiri, Roza; Zainal, Andri; Putra, Pasca Dwi; Suharianto, Joko (Universitas Negeri Medan, 2019)
The activities of the CPM with the title of “the Actualization of the Improvement of the Competitiveness of the Product Oil Scrub Traditional Herbs Through Branding and Certification Guarantee the Quality of Products UMK Rambal Deli in District Girders” this is focused on penuntasan 3 (three) problems specific be problem specific namely (1) Absence of the actualization of the knowledge explicit (explicit knowledge) in the product oil rub the traditional herbs that is produced; (2) product competitiveness the relative weakness with the management of production, marketing and finance is still traditional and; (3) the Body efforts yet there the body order official and permit the efforts which have not yet registered. Partners involved in the activities of the CPM this is the UMK Rambal Deli led by Mr. Agus Hidayat. UMK is located in the Street Sergeant M. Arifin gg. Muslim Lk. II wards Girders of the City, Subdistrict Girders, Regency of Deli Serdang. As an alternative solution for the settlement of the problem referred to consists of: (1) documentation of the profile and the formula of the products in print and electronic; (2) modernization and amplification of diffuse marketing: finishing and marketing system, and; (3) the assitance management certificate stand SME and business licenses. The activities of the CPM this will produce some external of them: The Proceedings, the Application of ABOUT and Product Innovation, draft pocket book, assitance management certificate stand order and clearance order.Keywords: SME, Certificate of Incorporation, Business license, Packaging.